Comparing physicochemical properties, antioxidant capacity and total phenolic content between homemade and commercial dates (phoenix dactyliferal l.) vinegar - Wyn, Saw Jo (Universiti Sains Malaysia, 2015)
Dates (Phoenix dactyliferal I) is a popular dried fruit being consumed in Malaysia especially during Ramadan month. Previous studies evidenced that dates possessed antioxidant properties. Various dates’ by-products have been produced to provide alternative food choices such as dates’ vinegar. However, limited study has been carried out on dates by-products especially dates’ vinegar. The aims of this study is to determine and compare the physicochemical properties, antioxidant properties, and total phenolic content of both homemade and commercial dates’ vinegar, hence providing additional scientific evidence of its potential. Preparation of homemade dates’ vinegar was done through spontaneous and simultaneous fermentation cycle process of semisoft and soft date cultivars at 28°C for 60 days. Physicochemical properties such as total sugar content, pH and total titratable acidity of homemade and commercial dates’ vinegar were then studied. Folin-ciocalteu reagent was used to examine their total phenolic content while hydrogen peroxide scavenging test and metal chelating test were used to screen the antioxidant capacity. Both homemade and commercial dates’ vinegar showed significant differences in physicochemical properties (p<0.05). Total phenolic content of dates’ vinegar ranged from 281.17 GAE/L to 641.17 GAE/L with significant differences noted between homemade and commercial dates’ vinegar (p<0.05). Hydrogen peroxide scavenging activity of semisoft dates’ vinegar [310.20 AAeq (pg/ml)], soft dates’ vinegar [200.06 AAeq (pg/ml)] and commercial dates’ vinegar [190.81 AAeq (pg/ml)] did not show any significant difference (p>0.05). Pearson’s correlation statistical test showed no